Frequency, Etiology, and Outcomes of Respiratory Distress in Term and Preterm Neonates Admitted to a Tertiary Care NICU. - Haroon, Asma; Nisa Malik, Noor Un; Aziz, Musfirah; Afridi, Saleha; Faisal, Sanober; Saad, Sarah (Journal of Neonatal Surgery, 2025)
Background: Neonatal respiratory distress (NRD) remains a major cause of neonatal morbidity and mortality, especially in low- and middle-income countries. This study aimed to determine the frequency, etiological distribution, and outcomes of term and preterm neonates presenting with respiratory distress in a tertiary NICU. Methods: A descriptive prospective study was conducted over six months in the NICU of Shifa International Hospital, Islamabad. A total of 160 neonates with clinical signs of respiratory distress were enrolled via consecutive sampling. Exclusion criteria included congenital lung anomalies and major cardiac malformations. Gestational age, clinical features, investigations, etiology, respiratory support details, and outcomes were recorded. Data were analyzed using SPSS v20. Associations were tested using Chi-square; a p ≤ 0.05 was considered significant. Results: Among 160 neonates, 91 (56.9%) were preterm. The most common etiologies of respiratory distress were respiratory distress syndrome (RDS) (22.5%), neonatal sepsis (21.9%), congenital pneumonia (19.4%), transient tachypnea of the newborn (TTN) (18.1%), and meconium aspiration syndrome (MAS) (18.1%). Overall mortality was 63.8%, significantly higher in preterm neonates (p < 0.01). Male gender and low birth weight were associated with increased risk of severe distress and adverse outcomes. Early respiratory support modalities varied from nasal oxygen to mechanical ventilation. Conclusion: RDS, sepsis, and pneumonia remain leading causes of NRD, with high mortality in preterm infants. Enhanced perinatal care, early diagnosis, and optimized respiratory support strategies are essential to improve outcomes in tertiary NICU settings.